2021
DOI: 10.1021/acsami.1c02987
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-Based Contractility Screening, a Reference-Free Alternative to Traction Force Microscopy Methodology

Abstract: The sensing and generation of cellular forces are essential aspects of life. Traction force microscopy (TFM) has emerged as a standard broadly applicable methodology to measure cell contractility and its role in cell behavior. While TFM platforms have enabled diverse discoveries, their implementation remains limited in part due to various constraints, such as time-consuming substrate fabrication techniques, the need to detach cells to measure null force images, followed by complex imaging and analysis, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The substrate strain energy W S is easily experimentally measured and is often reported as a measure of mechanical activity, see e.g. [11][12][13][14]. The active work done W CA is also clearly important as it can be conceptually linked to the energy that is required to drive the cell into its contractile state, with hard constraints on its possible size [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The substrate strain energy W S is easily experimentally measured and is often reported as a measure of mechanical activity, see e.g. [11][12][13][14]. The active work done W CA is also clearly important as it can be conceptually linked to the energy that is required to drive the cell into its contractile state, with hard constraints on its possible size [15].…”
mentioning
confidence: 99%
“…Although changes in traction forces are typically measured in mechanostransduction studies, recent work suggests that substrate strain energy can be used as a measure for mechanical activity [11, 12]. It has been suggested that cells may respond to directly changes in substrate strain energy [13].…”
mentioning
confidence: 99%
“…Compliant polydimethylsiloxane (PDMS) substrates of known stiffness were prepared as previously described ( Yoshie et al, 2019 ; Ghagre et al, 2021 ). In brief, parts A and B NuSil 8100 (NuSil Silicone Technologies, United States) were at 1:1 w/w ratios.…”
Section: Methodsmentioning
confidence: 99%
“…DNA force-based sensors can measure precisely the maximal force produced by cells, but not the lower values, and in addition, do not provide information about force directionality (Wang and Ha, 2013). Global or local deformations of micropatterned cells are not precise enough to investigate the finer aspects of how traction force is regulated (Tseng et al, 2011;Pushkarsky et al, 2018;Ghagre et al, 2021). Hence, alternative methods are required to evaluate the relationship between traction force and the biochemical composition of the cytoskeletal network in the same cell.…”
Section: Introductionmentioning
confidence: 99%